1996
DOI: 10.1007/bf02367107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of larval trematodes on the survival rates of two species of mud snails (hydrobiidae) experimentally exposed to desiccation, freezing and anoxia

Abstract: Digenetic trematodes are widespread among mud snails (Hydrobiidae) living in coastal lagoons and estuaries, but knowledge is generally lacking on their impact on these host organisms. We examined the survival rates of infected and non-infected experimental populations of two mud snail species, Hydrobia ventrosa (Montagu) and Hydrobia neglecta Muus, exposed to desiccation, freezing and anoxia in the laboratory. Our experiments indicated that non-infected groups of both species had similar survival rates after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Huynh-Feldt correction was used to calculate degrees of freedom for the withinsubjects tests after the production of transmission stages begins. As our results indicate, pathogenic eects of castration may increase host mortality at least at the late stage of infection, which is in accordance with the results of several previous studies (Meuleman 1972;Becker 1980;Lauckner 1986;Sousa and Gleason 1989;Jonsson and Andre 1992;Laerty 1993;Jensen et al 1996).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Huynh-Feldt correction was used to calculate degrees of freedom for the withinsubjects tests after the production of transmission stages begins. As our results indicate, pathogenic eects of castration may increase host mortality at least at the late stage of infection, which is in accordance with the results of several previous studies (Meuleman 1972;Becker 1980;Lauckner 1986;Sousa and Gleason 1989;Jonsson and Andre 1992;Laerty 1993;Jensen et al 1996).…”
Section: Discussionsupporting
confidence: 94%
“…This may lead to decreased survival of the snail host, at least in extreme environmental conditions (Meuleman 1972;Becker 1980;Lauckner 1986;Sousa and Gleason 1989;Jonsson and Andre 1992;Laerty 1993;Jensen et al 1996;Mouritsen et al 1997). These eects have been reported either for a speci®c host-parasite relationship (Meuleman 1972;Becker 1980;Jonsson and Andre 1992;Jensen et al 1996;Mouritsen et al 1997), or for a whole community of parasite species (Lauckner 1986;Laerty 1993). Additionally, Sousa and Gleason (1989) found that the four most common shedding parasites diered in their level of induced host mortality when the host was stressed in anoxic conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Infection with the isopod Bopyroides hippolytes reduced tolerance to salinity change in the kelp shrimp Eualus suckleyi (Moles & Pella 1984). Gastropods infected with larval digeneans were less resistant to dessication and hypoxia (Jensen et al 1996, Wegeberg & Jensen 1999. Lastly, juvenile Chinook salmon Oncorhynchus tshawystscha infected with metacercariae of the trematode Nanophyetus salmonicola exposed to PCBs suffered higher mortalities when challenged with the pathogenic bacterium Listonella anguillarum (Jacobson et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was particularly elevated at Merja Zerga due to low mortality in a high biomass context. The vulnerability of cockles from Merja Zerga compared to Arcachon was certainly due to interaction with other factors such as temperature (Jensen et al, 1996), Morocco being at the southern limit of C. edule distribution (Gam et al, 2008). The arrows indicate when the decrease between successive months is significant.…”
Section: Discussionmentioning
confidence: 99%